User-perceived reliability of shared protection systems with the Erlang type-k repair scheme. (1st January 2011) - Ozaki, Hirokazu; Kara, Atsushi; Cheng, Zixue
This paper describes the availability and mean time to first failure (MTTFF) of M-for-N shared protection systems (with M + N units) from the viewpoint of an arbitrary one of the N end users. Various forms of M-for-N shared protection are used to improve the reliability of telecommunication network devices such as access node devices, routers, switches, servers, network address translators, etc. In this paper, the time between failures of units and the time for repair are assumed to be an exponential distribution and the Erlang type- k distribution respectively. We consider the Erlang type- k distribution because repair time does not necessarily follow the exponential distribution and the Erlang type- k distribution is more flexible and useful for determining the system parameters such as the mean repair time and the variance based on the reliability objectives. The purpose of this paper is to evaluate the user-perceived reliability of such systems in a quantitative manner.